Plz Give answer (try to give it in picture.
Attachments:
![](https://hi-static.z-dn.net/files/d44/b9c4f0b0f42b448493203d054c1d64bf.jpg)
Answers
Answered by
2
hope it works...........
Attachments:
![](https://hi-static.z-dn.net/files/d06/c6006390732fa6f3276de8e293d68d5a.jpg)
Answered by
1
Solution:'
given by:-
![\frac{ {x}^{2} }{ {a}^{2} - {b}^{2} } = \frac{a + b}{a - b} \\ {x}^{2} = {(a +b) }^{2} \\ x = a + b \frac{ {x}^{2} }{ {a}^{2} - {b}^{2} } = \frac{a + b}{a - b} \\ {x}^{2} = {(a +b) }^{2} \\ x = a + b](https://tex.z-dn.net/?f=+%5Cfrac%7B+%7Bx%7D%5E%7B2%7D+%7D%7B+%7Ba%7D%5E%7B2%7D+-++%7Bb%7D%5E%7B2%7D++%7D++%3D++%5Cfrac%7Ba+%2B+b%7D%7Ba+-+b%7D++%5C%5C++%7Bx%7D%5E%7B2%7D++%3D++%7B%28a+%2Bb%29+%7D%5E%7B2%7D++%5C%5C+x+%3D+a+%2B+b)
given by:-
Similar questions